Association between infections and functional somatic disorders: a cross-sectional population-based cohort study. Issue 11 (2nd November 2022) - Schovsbo, Signe Ulfbeck; Møllehave, Line Tang; Petersen, Marie Weinreich; Ahrendt Bjerregaard, Anne; Eliasen, Marie; Pedersen, Susanne Brix; Eplov, Lene Falgaard; Kårhus, Line Lund; Fink, Per; Linneberg, Allan; Dantoft, Thomas Meinertz; Jørgensen, Torben; et al.
Abstract : Objectives: It has been suggested that infections can trigger functional somatic disorders (FSD). However, current evidence is limited by inconsistent findings in smaller studies conducted in clinical settings within selected populations and short follow-up times. We aimed to test the hypothesis that former infections are associated with FSD using data from nationwide registries and a large population-based cohort study, the Danish Study of Functional Disorders study. Design: FSD cases were identified in a cross-sectional population-based cohort and linked retrospectively to former hospital contacts with infections identified in the Danish National Patient Registry. The associations between FSD and former infections within 17 years were analysed using logistic regressions to calculate ORs and 95% CIs adjusted for age, sex and subjective social status. Setting: A population-based cohort in Denmark examined between 2011 and 2015. Participants: A total of 9656 men and women aged 18–76 years. Main outcome measures: FSD measured by various delimitations, including bodily distress syndrome (BDS), irritable bowel (IB), chronic fatigue (CF), chronic widespread pain (CWP), and multiple chemical sensitivity (MCS). Results: Overall, infections were associated with increased risk of all delimitations of FSD. The associations were more pronounced for multisystemic FSD. The number of prior infections increased the risk in a dose-response manner (p<0.0001). Bacterial but not viral infections were significantly associated with BDS (OR 1.69 (95% CI 1.46 to 1.96)), IB (OR 1.41 (95% CI 1.06 to 1.88)), CWP (OR 1.47 (95% CI 1.13 to 1.90)) and CF (OR 1.62 (95% CI 1.34 to 1.96)), but not MCS. Conclusion: Former infections leading to hospital contacts were associated with a higher risk of having FSD. These associations were more pronounced for bacterial than viral infections, and more infections increased the risk in a dose-response manner. These results tend to support the idea that severe infections could play a role in FSD.